Intracellular growth of Trypanosoma cruzi in cardiac myocytes is inhibited by cytokine-induced nitric oxide release - Fichera, Laura E. (2004)
Fil: Fichera, Laura E. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología Dr. Mario Fatala Chaben; Argentina.